The Impact of Project Based Learning on Enhancing Entrepreneurial Competencies in High School Vocational Education - Putri, Diana (CV. ULIL ALBAB CORP, 2026)
This study investigates the effectiveness of the Project-Based Learning (PjBL) model compared to conventional methods in enhancing the entrepreneurial competencies of high school/vocational high school (SMA/SMK) students in Indonesia. Conventional learning models often fail to equip students with crucial 21st-century skills, such as problem-solving and risk-taking, contributing to a high unemployment rate among vocational graduates. Adopting a pretest-posttest control group experimental design, 60 students (PjBL experimental group and conventional control group) were assessed for their cognitive skills and affective aspects of entrepreneurship. The Independent t-test analysis revealed a statistically significant difference (p<0.05) in the average gain score between the PjBL group (23.35) and the conventional group (8.05). This result confirms that PjBL is substantially more effective in improving both technical skills (such as business planning) and affective aspects (motivation, initiative, and self-confidence). Further qualitative observations indicated that PjBL facilitates the development of crucial soft skills, including collaboration, communication, and critical thinking. By providing an authentic and collaborative learning platform, PjBL successfully bridges the gap between theory and practice, serving as a catalyst for cultivating the mindset and skills necessary for young entrepreneurs.